Descending control systems - Dubner, Ronald (Henry Stewart Talks, 2009)
Sensory modulation, Activity dependent plasticity, Descending modulation: facilitation or inhibition?, Effects of RVM lesion on behavior, Dynamic shifts in descending modulation after inflammation, Experimental set up, NMDA receptor ion channel complex, Changes in NMDA receptor subunit expression in the RVM, Changes in NMDA receptor protein expression in the RVM, Changes in NMDA NR2 receptor subunit phosphorylation after inflammation, Neuronal activity in the RVM, Changes in RVM neuronal activity during the development of inflammation, Brain-derived neurotrophic factor (BDNF), Normal function of the brain
Archived at 2021/07/28